Dynamic Trajectory of Long-Term Cognitive Improvement Up to 10 Years in Young Community-Dwelling Stroke Survivors: A Cohort Study - Elgh, Eva; Hu, Xiaolei (Frontiers in Neurology, 2019)
Background and objective The trajectories of long-term and domain-specific cognitive alterations over a decade after stroke are largely unknown. This study aims to investigate the dynamic alterations of domain-specific cognitive performance among young stroke survivors over ten years after their first stroke. Methods A prospective cohort study was carried out on 38 young stroke survivors (aged 18–65 at stroke onset) living in the community at ten years after their first stroke. The cognitive outcomes were assessed repeatedly at one week, seven months, and ten years after their first stroke on the sub-domains: process speed (Symbol search and Coding from WAIS, TMT-A), visual attention (Bells test), visuospatial function (Block design from WAIS, RCFT), executive function (TMT-B, verbal fluency), verbal function (Letter fluency (FAS) from D-KEFS and CD), working memory (Digit Span from WAIS), immediate memory (RCFT and CD), and delayed memory (RCFT and CD). Global cognition was evaluated with Mini mental state examination at the two later time-points. Results We found a delayed significant improvement of working memory with total recovery ten years after participants’ stroke. Visuospatial function recovered already at seven months and remained stable at 10-year follow-up. Process speed demonstrated a significant decrease at ten years compared to seven months after stroke onset, a decrease which could be compensated by enhancements of other cognitive domains. No further deterioration was found in verbal function, immediate- and delayed memory, and executive function during 10-year follow-up. Global cognition improved by on average two points between seven months and ten years. Education level and fatigue showed low to moderate positive correlations with cognitive improvements. Conclusions The concordance of cognitive improvements between domain-specific and global cognitions strongly suggest that some young stroke survivors do improve their cognitive outcome over a 10-year period following their first stroke. This finding fills a gap of knowledge with respect to the dynamic trajectory of post-stroke cognition, with important implications in clinical practice.